Phase morphology and crystallinity of poly(vinylidene fluoride)/poly(ethylene oxide) piezoelectric blend membranes - Tamaño-Machiavello, M. N. (2015)
Polymer blends based on poly(vinylidene fluoride), PVDF and poly(ethylene oxide), PEO, with varying compositions have been prepared by solvent casting, the polymer blend films being obtained from solutions in dimethyl formamide at 70ºC. Under these conditions PVDF crystallizes from solution while PEO remains in the molten state. Then, PEO crystallizes from the melt confined by PVDF crystalls during cooling to room temperature. PVDF crystallized from DMF solutions adopt predominantly the electroactive β-phase (85%). Nevertheless when PEO is introduced in the polymer blend the β-phase content decreases slightly to 70%. The piezoelectric coefficient (d33) in pristine PVDF is -5 pC/N and decreases with increasing PEO content in the PVDF/PEO blends. Blend morphology, observed by electron and atomic force microscopy, shows the confinement of PEO between the already formed PVDF crystals. On the other hand the sample contraction when PEO is extracted from the blend with water (which is not a solvent for PVDF) allows proving the co-continuity of both phases in the blend. PEO crystallization kinetics have been characterized by DSC both in isothermal and cooling scans experiments showing important differences in crystalline fraction and crystallization rate with sample composition.